The Importance of Applying Total Quality Management in Saudi Arabia Colleges of Technology from the Perspective of Training Staff Members - Mohamed Hadi Ali Al-Fagih (University of Science and Technology, Yemen, 2015)
The main objectives of the current study is to identify the opinions of the training staff members in technical colleges towards the importance of applying total quality management in such colleges; and the availability of human, material and organizational resources that are necessary for applying total quality management in such colleges; and determine the statistically significant differences in the opinions of the training staff members in such technical colleges towards the study variables. A field study has been applied to four technical colleges in Abha, Jazan, Algunfotha and Najran. A questionnaire has been used to collect information and analyze data statistically. The study concluded that the respondents consider the importance of applying total quality management in such colleges as high. As for the availability of human, material and organizational resources that are necessary for applying total quality management in such colleges, the respondents considered it as average. There are statistically significant differences in the aspect of importance of applying total quality management in such colleges by location of college, and by attending training courses/workshops in the field of total quality. Also, there are statistically significant differences in the aspect of availability of human resources by attending training courses in the field of total quality. Moreover, there are statistically significant differences in the aspect of organizational resources by location of college. Keywords: Higher Education, Colleges of Technology, Total Quality Management, Saudi Arabia.